The use of controlled punishment and ritual in couples therapy - Lynch, B.J. (The Therapist's Notebook: Homework, Handouts, and Activities for Use in Psychotherapy, 2013)
Couples who come into therapy with amorphous symptoms often reveal later in treatment that there has been a traumatic event that occurred in the past and that has lingered as a significant disturbance to intimacy. No amount of “talk therapy? or insight seems to allow these couples to move past the point of emotional treachery. This activity is designed to allow these couples a vehicle for putting the past to rest in a way that allows them to continue their relationship without resentment, revenge, or continual pain. © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.mft